2014
DOI: 10.1039/c4cc05397d
|View full text |Cite
|
Sign up to set email alerts
|

A convenient sol–gel approach to the preparation of nano-porous silica coatings with very low refractive indices

Abstract: Silica coatings with refractive indices as low as 1.10 were prepared via a one-step base-catalysed sol-gel process using methyltriethoxysilane and tetraethoxysilane as co-precursors. No expensive equipment was required and the method did not require etching or high-temperature calcination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…The most difficult task is to prepare the top layer film with ultra-low refractive index of 1.10. In our previous work, we reported that using MTES and TEOS as co-precursor under base-catalyzed condition could decrease the refractive index of silica film to as low as 1.10 [26], seemingly appropriate to be applied for the designed top layer film. However, the well-adjusted three-layer coating presented a relatively low transmittance of 98.8 % at 355 nm (as seen in Figure S1), too low to meet the rigorous requirement in high-power laser systems.…”
Section: Refractive Index Of Each Layer Of the Three-layer Ar Coatingmentioning
confidence: 99%
“…The most difficult task is to prepare the top layer film with ultra-low refractive index of 1.10. In our previous work, we reported that using MTES and TEOS as co-precursor under base-catalyzed condition could decrease the refractive index of silica film to as low as 1.10 [26], seemingly appropriate to be applied for the designed top layer film. However, the well-adjusted three-layer coating presented a relatively low transmittance of 98.8 % at 355 nm (as seen in Figure S1), too low to meet the rigorous requirement in high-power laser systems.…”
Section: Refractive Index Of Each Layer Of the Three-layer Ar Coatingmentioning
confidence: 99%
“…Solar energy, among several other alternative energy sources, has been attracting interest in various application elds because of its abundance, cost-effective production, and environmental friendliness. [4][5][6][7] However, to directly fabricate the nanostructures on substrates, nanopatterning (e.g., electron-beam, nanoimprint, or laser interference lithography) and etching processes including chemical and heat treatments are required, which increase the fabrication cost and complexity. [1][2][3] However, the power conversion efficiencies (PCEs) of DSSCs fall below 13%, mainly due to limitations including the light absorption of the dyes and the interface charge separation between dyes and titanium dioxide (TiO 2 ) electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…The image of the SiO 2 ‐solgel (Figure B) displays aggregation morphology which is mainly composed of irregular or flake or nanoparticle units. This morphology can partly be contributed to the formation mechanism of solgel methods . In this work, silica sol which was stabilized by ammonium hydroxide was used as precursor, when adjusting the pH of the solution to 5.5, the free hydroxyl groups begin to dehydrate to form silica sub‐particles or larger molecules, these sub‐particles gradually grow and aggregate and finally come into bigger particles .…”
Section: Resultsmentioning
confidence: 99%